Cognitive motor intervention for gait and balance in Parkinson's disease: systematic review and meta-analysis. (February 2016) - Wang, Xue-Qiang; Pi, Yan-Ling; Chen, Bing-Lin; Wang, Ru; Li, Xin; Chen, Pei-Jie
Objective: We performed a systematic review and meta-analysis to assess the effect of cognitive motor intervention (CMI) on gait and balance in Parkinson's disease. Data sources: PubMed, Embase, Cochrane Library, CINAHL, Web of Science, PEDro, and China Biology Medicine disc. Methods: We included randomized controlled trials (RCTs) and non RCTs. Two reviewers independently evaluated articles for eligibility and quality and serially abstracted data. A standardized mean difference ± standard error and 95% confidence interval (CI) was calculated for each study using Hedge's g to quantify the treatment effect. Results: Nine trials with 181 subjects, four randomized controlled trials, and five single group intervention studies were included. The pooling revealed that cognitive motor intervention can improve gait speed (Hedge's g = 0.643 ± 0.191; 95% CI: 0.269 to 1.017, P = 0.001), stride time (Hedge's g = -0.536 ± 0.167; 95% CI: -0.862 to -0.209, P = 0.001), Berg Balance Scale (Hedge's g = 0.783 ± 0.289; 95% CI: 0.218 to 1.349, P = 0.007), Unipedal Stance Test (Hedge's g = 0.440 ± 0.189; 95% CI: 0.07 to 0.81, P =0.02). Conclusions: The systematic review demonstrates that cognitive motor intervention is effective for gait and balance in Parkinson's disease. However, the paper is limited by the quality of the included trials.